ANALISA RUH PENDIDIKAN KARAKTER DALAM PENDIDIKAN NASIONAL (UNDANG-UNDANG 2003) - Syahrul Akmal Latif; Yusri Herman (UIR PRESS, 2016)
The issue of education is never over to talk about because education is one measurement of a person's individual accomplishments and achievements systematically nation. The high education of human resources will give a lot of useful works for the individual and social. Unfortunately, the education that was developed based on this character only strengthen individual and social, it’s beyond the divine value . It is due to the historical roots of the character education by Immanuel Kant (1724-1804) and Charles Renouvier (1815-1857); Religious morality in the low education and August Comter (1798- 1857); secular morality. Renouvier said the weakness of youth responsibility, loss of justice equality, respect and others. The process of character education is faced with the application of secularization. Such as, in France Francois Camille Jules Ferry (1832-1893) , a French Education minister said; Moral education is important but explicitely teaching morality does not needed. The development of character education in America is very dynamic. It’s started from 19th century (1900-1950) until 1997.It’s established nationally. Finally, Thomas lichona explained the entire role of religion in the education of character with seven steps and the role of teachers in character education. Thus, the author conducted religious analysis which widely spread among society is that the teaching of Protestant religious. But, It successfully gives individual and social value as character education. On the contrary, the goal of our national educational in 1945 (Version amendment) Article 31, paragraph 3 states: The Government shall manage and organize a national education system. Which increases the Faith and piety as well as noble character in order to educate the nation that adopted by law. Article 31, paragraph 5, states that the government advances science and technology to uphold the values of religious and national unity for the progress of civilization and prosperity of mankind. Likewise, the purpose of philosophy Nasionsl Education Act No. 20 of 2003. The 1945 Constitution and the Law N0 20 of 2003. Strongly reflects the value of belief in one God as the first principle of Pancasila as the first principle says it is an acknowledgment that in developing the nation's education should not be separated from human relations and slave relationship with God the creator.